The role of the political stability in the political system of society (Journal of Philosophy Culture and Political Science, 2015)
The article analyzes the phenomenon of political stability as a categoryof political science, and identifies the factors that affect the political stabilityof the society and provides its classification. The author also examinesthe importance of political stability in the sustained development of politicalsystem and of political regime. The paper also identifies the main aspectsof the relationship between political stability and of political culture.
Keywords: political stability; political culture; consensus; political values.